Choosing among competing blockbusters: Does the identity of the third-party payer matter for prescribing doctors? - Dag Morten Dalen; Enrico Sorisio; Steinar Strøm (Center for Economic Studies and ifo Institute (CESifo), 2010)
TNF-alpha inhibitors represent one of the most important areas of biopharmaceuticals by sales, with three blockbusters accounting for 8 % of total pharmaceutical sale in Norway. With use of a unique natural policy experiment in Norway, this paper examines to what extent the identity of the third-party payer affects doctors' choice between the three available drugs. We are able to investigate to what extent the price responsiveness of prescription choices is affected when the identity of the third-party payer changes. The three dominating drugs in this market, Enbrel, Remicade, and Humira, are substitutes, but have had different and varying funding schemes - hospitals and the national insurance plan. We find that treatment choices are price responsive, and that the price response is considerably higher when the doctor's affiliated hospital covers the cost instead of a traditional fee-for-service insurance plan. When the doctors' hospitals are covering the cost of this treatment instead of insurance the total cost of treatment is significantly reduced.
Keywords: C35; D43; I18; L11; 330; pharmaceuticals; discrete choice model; funding-schemes; Pharmazeutisches Produkt; Biotechnisches Produkt; Gesundheitskosten; Gesundheitsversorgung; Diskrete Entscheidung; Norwegen